2022
DOI: 10.1108/aeat-06-2021-0178
|View full text |Cite
|
Sign up to set email alerts
|

Aero-propulsive interaction model for conceptual distributed propulsion aircraft design

Abstract: Purpose This research aims to present an aero-propulsive interaction model applied to conceptual aircraft design with distributed electric propulsion (DeP). The developed model includes a series of electric ducted fans integrated into the wing upper trailing edge, taking into account the effect of boundary layer ingestion (BLI). The developed model aims to estimate the aerodynamic performance of the wing with DeP using an accurate low-order computational model, which can be easily used in the overall aircraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The aerodynamic performance of aircraft has also been improved due to the aero-propulsion coupling from DEP. The Europe program "Clean Sky 2" pointed out that the maximum lift coefficient could even reach 4.5 in the 2D scenario affected by ducted fans [7]. In addition, through wind tunnel tests and CFD computation [8], it is confirmed that DEP has the positive characteristics of increasing lift and reducing drag at low airspeed.…”
Section: Introductionmentioning
confidence: 94%
“…The aerodynamic performance of aircraft has also been improved due to the aero-propulsion coupling from DEP. The Europe program "Clean Sky 2" pointed out that the maximum lift coefficient could even reach 4.5 in the 2D scenario affected by ducted fans [7]. In addition, through wind tunnel tests and CFD computation [8], it is confirmed that DEP has the positive characteristics of increasing lift and reducing drag at low airspeed.…”
Section: Introductionmentioning
confidence: 94%